2012
DOI: 10.1111/j.1365-4632.2012.05641.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of human furuncular myiasis of Cordylobia anthropophaga (Grunberg) in Nigeria

Abstract: Two hundred people were randomly selected for myiasis infection in the Niger Delta region of Nigeria, except in some states where we did not get the stipulated number (200) to sample. In each of the six states sampled within the Niger Delta in 2009, 88% of 200 patients examined in Rivers State had the Cordylobia infection followed by Cross Rivers State (>86%), Bayelsa (>84%) while Edo, Delta, and Akwa Ibom states showed higher than 82% infection in that order. Our findings showed that women, children, and infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Lepidagathis alopecuroides [Vahl] and Bryllophyllum species are some of the Niger delta plants' extracts that had been used in the flushing of the serosanguinous fluid that is associated with Cordylobia anthropophaga larval extraction [Ogbalu et al,2012[Ogbalu et al, , 2013 In the present study, it exhibited its property as an antipyretic agent in the treatment of breast myiasis sores. The application of ethanolic extracts of A. Conyzoides resulted in relieving pains associated with breast myiasis sore and initiated closing of wound sites within 72 hours after application.…”
Section: The Use Of Ageratum Conyzoides L [Asteraceae] As a Therapeumentioning
confidence: 95%
“…Lepidagathis alopecuroides [Vahl] and Bryllophyllum species are some of the Niger delta plants' extracts that had been used in the flushing of the serosanguinous fluid that is associated with Cordylobia anthropophaga larval extraction [Ogbalu et al,2012[Ogbalu et al, , 2013 In the present study, it exhibited its property as an antipyretic agent in the treatment of breast myiasis sores. The application of ethanolic extracts of A. Conyzoides resulted in relieving pains associated with breast myiasis sore and initiated closing of wound sites within 72 hours after application.…”
Section: The Use Of Ageratum Conyzoides L [Asteraceae] As a Therapeumentioning
confidence: 95%
“…Myiasis is a type of parasitosis which involves the infestation of body tissues of humans and animals by dipteran larvae which feed on host's necrotic or living tissue, liquid body substances or ingested food (4,15,17). In a recent literature review, Singh et al (4) described approximately 37 different fly species belonging to ten families as responsible worldwide for the onset of human myiasis and the most frequently reported were those from the family Calliphoridae, Sarcophagidae, Oestridae, Muscidae, Psychodidae, Syrphidae, Phoridae, Drosophilidae, Dryomyzidae and Gasterophilidae.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has a worldwide distribution and has been endemic in Latin America and SSA for years. However, with the increase in global travel, the disease has spread widely, especially in areas with warmer temperatures and high humidity [ 5 ]. Myiasis is more common in animals, such as sheep, rodents, and antelope, than humans because humans are accidental hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Compelling scientific literature have revealed that a significant rise in temperature or humidity will increase the growth and redistribution of most myiasis-causing flies, subsequently increasing myiasis infestation in such regions [ 11 , 14 ]. Some factors that influence this dermatosis in SSA are high humidity and temperature (especially during the rainy season) [ 5 ]. Poverty, and poor hygiene also add to the vulnerability to human myiasis infestation.…”
Section: Introductionmentioning
confidence: 99%